Pitfalls of hip hop pedagogy: Re-examining and questioning the definition - Wei, Ming Tao; Yang, Zhi; Wang, Xin; Liu, Dan Xi; Bai, Yu Jie; Guo, Rui Yi; Yu, Ning; Ling, Xi (Frontiers in Psychology, 2023)
Recently, hip-hop pedagogy or Hip-Hop Based Education (HHBE) have become buzz words in the academic and public debate around hip-hop. However, we found that most definitions of hip-hop pedagogy are missing the concept of pedagogy itself. One consequence of failing to adequately explain the concept of pedagogy is that it may lead future hip-hop researchers, students, and teachers inadvertently to disseminate misinformation or foster unclear thinking by using “hip-hop pedagogy” in inaccurate or vague ways. For these reasons, it is important to have a shared understanding of hip-hop pedagogy. In this article, we present three updated, expanded definitions of hip-hop pedagogy with the potential for widespread acceptance. These definitions aim to convey in the simplest terms what hip-hop pedagogy is for the purpose of informing educators and preparing them to use data.